ECONOMIC REFORMS AND MICRO, SMALL AND MEDIUM ENTERPRISES - Kaur, Gurneet (International Journal of Research -GRANTHAALAYAH, 2017)
Micro, Small & Medium enterprises (MSMEs) have played a crucial role in the overall economic development of every developing economy in the world. In India, MSMEs have helped in creating a favourable environment of growth by serving as ancillary units to large scale industries. They not only create huge employment opportunities for the public but also address other challenges faced by the economy like poverty and removing regional imbalances. Keeping in view the crucial role of MSMEs in our economy, the present paper is an attempt to analyze the definition of MSMEs, the role and performance of MSMEs in Indian economy and government policies towards MSMEs as well as the various challenges and opportunities associated with MSMEs in India. The study reveals that over a period of time notable growth has been shown by the MSME sector which has been a leading contributor to export, employment and Gross domestic product in India. Therefore, some sincere action plan and their proper implementation is must for the encouragement of the MSMEs in the Indian economy.